The effect of government publicity and guidance on farmers’ ecological environment governance participation behavior—The mediating effect of environmental literacy and perceived value - Haoran Wei; Juan Yao; Fuhong Wang (PLoS ONE, 2025)
As an important policy tool for rural ecological environment governance, it is crucial to clarify the mechanism through which government publicity and guidance affects farmers’ participation behavior, thereby enhancing the effectiveness of rural ecological governance. Based on survey data from rural households in Changji Prefecture, Xinjiang, this study empirically examines the influence of government publicity and guidance on farmers’ decision-making behavior, protective behavior, and supervisory behavior related to ecological environment governance, employing an Ordered Probit model, OLS regression, and a Generalized Structural Equation Model. The findings indicate that: (1) Government publicity and guidance, Environmental literacy, and Perceived Value exert significant positive effects on farmers’ multidimensional ecological environment governance behaviors; (2) Heterogeneity analysis reveals that these three factors have a stronger promoting effect on the ecological environment governance behaviors of low-income farmers; (3) Environmental literacy and Perceived Value serve as significant mediators in the relationship between government publicity and guidance and farmers’ ecological environment governance participation behavior, and two together construct a chain mediation path of “government publicity and guidance-environmental literacy-perceived value-ecological and environmental governance behavior”. Based on these findings, this study proposes policy recommendations including refining government publicity and guidance strategies, systematically enhancing environmental literacy, facilitating the internalization of Perceived Value, and implementing differentiated policy support mechanisms.